PEMERIKSAAN DAN PENYULUHAN KESEHATAN DI PANTAI AIR MANIS PADANG - Maisharoh Maisharoh; Dian Sari; Rahmadhani Rahmadhani; Afika Rahma; Fianika Fianika (Jurnal Salingka Abdimas, 2022)
Health is a dynamic balanced state influenced by genetic, environmental, and daily lifestyle factors such as eating, drinking, working, resting, to managing emotional life. Health check is an examination that focuses on primary and secondary prevention efforts, namely detecting various health factors as a whole that can cause certain diseases in the future. A number of public health problems stem from the healthy behavior of the community and the influence of the socio-cultural system that becomes the values and beliefs of the local community. The purpose of community service activities is to make people understand the importance of health checks. The method used is the lecture and discussion method. The counseling activity was carried out in the Padang Air Sweet Beach area in September 2022. The activity was attended by lecturers, lecturer staff, as well as students and the community who were in the Padang Air Sweet Beach working area. The results of the examination activities showed that the community knew what factors were influencing various kinds of diseases that were often experienced by the community, including diabetes mellitus, gout and cholesterol and the impact that these diseases would have. The conclusion of this activity is that the public can know about the importance of carrying out regular and periodic health checks so as to increase optimal health.